(untitled) (Journal of the College of Basic Education, 2022)
Which included the first door on the definition of research include the introduction and the importance of research and the problem and where also included Search targets are: -The preparation of special education units by using the style of stations according to the exercises vision visual learning my skills in handling chest and scoring from the free throw line. -Recognize the effect of the style of stations according to the exercises visions, learning my skills in handling chest and scoring from the free throw line. The research hypotheses are: -There are significant differences between the results of the tribal tests and the results of the post tests of the experimental group and the control group in learning my skills scoring from the free throw line and handling thoracic basketball differences. -There are significant differences between the results of the post tests between the experimental group and the control group in learning my skills handling chest and scoring from the free throw line basketball and in favor of the experimental group differences. Also included areas of research. The second section covered a theoretical studies, a visual style stations, vision and skills of basketball under study. The third chapter evolved to include a research methodology where researchers used the experimental curriculum for suitability problem of search and selection of the sample purposively was where students grade the first stage Department of Physical Education and Sport Sciences basic Mustansiriya University Education Faculty for the academic year 2015- 2016. The total number (55) students have been choose the experimental group in a way the draw was where Hall (2) and numbered (20) students represented Hall (1) to the control group and the number of them (20), student and thus the sample of (40) students and thus accounted for (72.72%). And mayors of researchers from a homogeneity in Alantorpomitrih variables and then choose the appropriate tests to search and then deliberately researchers conduct the first exploratory experiment and a second exploratory test on a sample of the excluded students from the main trial and the number (6) students, as well as mayors researchers to conduct two units Tarevican staff assistant to learn the style of the stations, as well as how to perform exercises visions, and then deliberately researchers to conduct tribal tests and erected sports hall closed, Department of Physical Education and Sports Science Faculty of Basic Education, and later, the researchers deliberately to the use of private educational units and applied to the experimental group and by professors specialists, reaching the number of units overall educational (5 units) was applied educational exercise visions, the main lesson of the department of applied activity, After completing the application units deliberately researchers to conduct post tests by the same teachers and the same indoor sports hall was used statistical Pouch (SPSS) in order to extract the results. Part IV evolved to include a review of the tables, which included the results of the tests and tribal posteriori for the two experimental and control group of chest Mhartin handling and scoring from the free throw line as well as the results of the post tests posteriori between the experimental group and the control group and the experimental Mhartin control. The Title V evolved to include findings, recommendations and reach your search results, including: -The results showed superiority of the experimental group that used the style of exercise stations according to visions, to learn some basketball skills to the control group. -There is a preference to use the method according to the stations exercises visions for the style of the control group to learn the two skills (Handling chest and scoring from the free throw line). As for the recommendations. - The introduction of exercises visions, to learn other skills of basketball and in other games